Attitudes of High School Students Regarding Intimate Relationships and Gender Norms in New Providence, The Bahamas - Nicolls, Donna; Russell-Smith, Camille; Dean-Patterson, Sandra; Deveaux-Stuart, Lindel D.; Gibson-Mobley, Ingrid; Williams, Elizabeth J.; Pinder-Darling, Antoinette; Fielding, William J. (International Journal of Bahamian Studies, 2014)
This paper reports the attitudes and actions on relationships with the opposite sex of 1,002 Grade 10 and Grade 12 students in New Providence. Girls were more likely than boys to use aggressive behaviours in teen relationships. Some of the behaviours noted in teen relationships informed expectations of marital relationships, such as restricted access to friends of the opposite sex. The students endorsed a number of sex-related stereotypes, such as a man being the head of the household. Both male and female students indicated that it was acceptable for men to control their wives. Participation in aggressive and controlling behaviours by teens points to the need to educate students about how to develop more respectful relationships.